Improving The Availability Of Automatic Surface Grinding Machines Through A3 Problem Solving, SMED, And Spare Part Control In The Manufacturing Industry - Entis Sutisna Entis; Alifvio Iyayu Kamsi; Muhammad Khosim Adha; Muhammad Sultan Rifal (CV. AFDIFAL MAJU BERKAH, 2026)
Machine availability is a critical indicator for assessing production asset readiness. This study aims to improve the availability of an automatic surface grinding machine in a tooling area of an electronic component manufacturing company using the A3 problem-solving approach. Machine Operation Data from April-June 2024 showed an initial availability of 34.3%, with an average actual running time of 18,287 minutes against an average planned production time of 53,238 minutes. Breakdown analysis identified two dominant losses: stop waiting operator at 15,135 minutes and stop waiting spare part at 7,680 minutes, contributing 22,815 minutes (93.6%-94.0%) of the total breakdown time. This research employed a descriptive quantitative case study through problem clarification, problem breakdown, target setting, root cause analysis, countermeasure development, implementation, and result monitoring. The main countermeasures included allocating supporting manpower during early-shift setup, reviewing process planning, preparing Single Minute Exchange of Dies (SMED) implementation, coordinating machine component improvement, and establishing a spare part list with minimum stock control. The monitoring result showed that the average availability during September-November 2024 reached 58.7%, an improvement of 24.4 percentage points from the baseline. Stop waiting operator decreased to an average of 4,490 minutes and stop waiting spare part decreased to 0 minutes in the after period. The findings indicate that A3 problem solving combined with changeover and spare part control can significantly improve machine readiness. This study contributes to data-driven continuous improvement practices for enhancing manufacturing equipment performance.